Konflik Hak dan Kewajiban dalam Perjanjian Digital Saat Janji Hukum Tak Seindah Kenyataan - Isnaeni, Yuliasara; Rasnoto; Indriasari, Evy; Dilaga, Tirta Prasetya (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The advancement of digital technology has transformed legal interactions in agreements between users and digital service providers. However, in practice, there is often an imbalance between the rights and obligations of the parties, where the legal promises stated in the agreement do not always align with their actual implementation. This study aims to analyze conflicts of rights and obligations in digital agreements and their impact on legal protection for users. This research employs a qualitative method with a literature study (library research) approach to examine various legal sources, including legislation, court decisions, and academic literature related to digital agreements. The findings indicate that digital agreements are often unilaterally drafted by service providers with standard clauses that tend to favor one party. This imbalance potentially violates the principle of contractual fairness and weakens legal protection for users. Furthermore, the implementation of rights and obligations in digital agreements is often hindered by users' lack of understanding of contract terms, weak law enforcement mechanisms, and the dynamic nature of digital sector regulations. Therefore, efforts are needed to strengthen digital agreement regulations, enhance users' legal literacy, and promote the application of transparency and fairness principles in drafting digital contracts. By doing so, conflicts over rights and obligations in digital agreements can be minimized, ensuring that legal promises are not merely formalities but provide real protection for all parties involved.